2015
DOI: 10.3233/jae-140123
|View full text |Cite
|
Sign up to set email alerts
|

Highly uniform single-sided portable NMR sensor and its application in assessing the aging level of silicone rubber insulators

Abstract: This study presents a high-performance single-sided portable nuclear magnetic resonance (NMR) sensor. The magnet array, which is composed of five identical cuboid permanent magnet blocks and two passive shimming sheets, generates a highly uniform B0 field in a 10 × 10 mm 2 lateral area. Along the two orthogonal lines in this lateral area, the measured B0 strength variation is less than 338 ppm. Vertically, the measured B0 magnitude decreases from 144.387 mT to 130.603 mT, with a constant gradient of 4.6 T/m fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The novel Halbach magnetic field generator (Fig. 4 a, b) was developed by our group, in collaboration with the Electrical Engineering College of Chongqing University [ 20 , 21 ]. The novel magnetic field generator is composed of nine identical cuboid permanent magnet modules and two passive shimming sheets (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The novel Halbach magnetic field generator (Fig. 4 a, b) was developed by our group, in collaboration with the Electrical Engineering College of Chongqing University [ 20 , 21 ]. The novel magnetic field generator is composed of nine identical cuboid permanent magnet modules and two passive shimming sheets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The novel magnetic field generator (Fig. 4 ) was developed by our group in collaboration with the Electrical Engineering College of Chongqing University [ 20 , 21 ]. We used the 3D CAD image to show the magnet arrangement of the uniform magnetic field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the ratio further increased to 3, the B 0 profile generated an arms-up parabola along the y -axis, which showed that an optimum ratio of a/b existed for a constant field along y . The optimal procedure was similar to that in [25]. …”
Section: Sensor Designmentioning
confidence: 99%
“…The relative position of the three magnets was adjusted to optimize the homogeneity of the B 0 in the region of interest (a 4 mm × 4 mm × 4 mm area which is 5 mm above the surface of the central magnet), and the optimal structure of the magnet body was determined after. The optimization process was described in the reference [21] in detail. For the optimal magnet structure, Figure 3 shows the variation of B 0 along y axis at different z simulated by Maxwell 3D (Ansoft, Pittsburgh, PA, USA).…”
Section: Structure Of the Magnet Bodymentioning
confidence: 99%